PENGALAMAN IBU DALAM MENGHADAPI ANAK REMAJA DENGAN GEJALA PREMENSTRUAL DYSPHORIC DISORDER - Tri Kesuma Dewi; Purwanta Purwanta; Elsi Dwi Hapsari (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Mothers experience dealing an adolescent with premenstrual dysphoric disorder symptomsPurposeThe purpose of this study is to explore mothers experience dealing an adolescent with symptoms of the premenstrual dysphoric disorder (PMDD). MethodsThe research used quantitative and qualitative methods. In the quantitative method used with a cross-sectional design using the PMDD symptom questionnaire according to DSM-IV in adolescents, while in a qualitative method using in-depth interview technique on the mother of the adolescent. Data analysis on a quantitative method using descriptive analysis while on qualitative using method of data analysis Colaizi (1973). ResultsThis study showed that 23% or 52 of 226 adolescents had PMDD symptoms and found five themes: 1) the mother knew and felt the symptoms of PMDD experienced by the child, 2) The attitude and the limited time of mother and child affected the delivery of PMDD symptoms of the child to the mother, 3 ) Diversity of the mother's response when the child is facing symptoms of PMDD, 4) The handling that the mother gives to the child when the child has PMDD symptoms is sourced from the past, 5) Mother seeks information about the handling that can be done when experiencing PMDD symptoms. ConclusionMothers play an important role in helping adolescent deal with PMDD symptoms. mothers can provide support, be it instrumental support, assessment, emotional and informational. Mothers should have adequate knowledge of PMDD symptoms so that the support provided can be maximized.